ANALISIS SERVICE EXPERIENCE DALAM MENCIPTAKAN KEPUASAN PENUMPANG KERETA WISATA PT. KERETA API PARIWISATA (Survei Pada Wisatawan Domestik Kereta Wisata Bali, Kereta Wisata Toraja, Kereta Wisata Nusantara PT. Kereta Api Pariwisata) - Sari, Wulan; Wibowo, Lili Adi; siswhara, Gita (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
PT. Kereta Api Pariwisata is one of subsidiaries of PT. Kereta Api Indonesia (Persero), which manages business travel services and tour-based railroad. PT. Kereta Api Pariwisata has thre tourism trains such Bali tourism train, Toraja tourism train, and Nusantara tourism train. The third tourism train offers comfort and beauty of the theme of culture of Bali, Toraja, and Nusantara that can provide a service experience to passengers is expected to create a tourism train passenger satisfaction PT. Kereta Api Pariwisata. The theory of service experience that is used by Knutson et al., In Identifying the Dimensions of the Experience Construct. Journal of Hospitality Leisure Marketing (2006:39) with dimensions used are incentive, accessibility, convenience, utility, environment, benefits, and trust. Theory of satisfaction is a composite theory of Kotler (2009:164) with dimensions of performance and importance to the theory Hatane Semuel (2009:30) which states "Important Necessary-performance analysis, namely by conducting a survey of the passengers to know the expectations of passengers against the interests of each attribute and the level of satisfaction derived from the actual service." So the dimensions of satisfaction used was the performance, importance , and expectations. The premise which supporting this study is from Debra Grace, Aron O'cass (2004), Hoi Mun (2006), and Nigel Hill, Rachel Allen (2007). Based on the above explanation, the research about on service experience analysis in creating a tourism train passenger satisfaction PT. Kereta Api Pariwisata. This research is using descriptive and verificatife with is an explanatory method survey sampling technique with accidental sampling (convenience sampling) technique, and the number of samples of 115 respondents. Analysis technique data in using Path Analysis with the help of software SPSS 15.0 computer interview, and quesioner as data collection techniques. The Findings showed that, the analysis of service experience through the incentive dimension, accessibility, convenience, utility, environment, benefits, and trust have influence over the passenger’s satisfaction. Former of need dimention wich have the highest influence isbenefit and accessibility dimension have a little significant impact on passenger’s satisfaction. As for the highest passenger tourism train satisfaction perceived to the dimensions of benefit. That means that passengers need the advantage of everything they done and easy access make the passengers feel the comfort of the tourism train. Limitations in this research that this study just conducted a survey to domestic passengers of tourism trains. Therefore, further research is expected to examine the foreign tourism train passenger satisfaction.